The Effectiveness of Education with Video in Increasing Family Support and Compliance with Treatment for Hypertension Patients - Masnah, Cek; Suharti, Suharti; Heryani, Erna; Berliana, Novi (Poltekita: Jurnal Ilmu Kesehatan, 2024)
Hypertension is a national problem in Jambi Province and East Tanjung Jabung Regency. This situation is exacerbated by low regularity of taking medication in East Tanjung Jabung Regency (39.07%), which is far below the national figure of 54.40%. The behavior of taking medication regularly is closely related to a person's adherence to following recommended or prescribed treatment process. In this regard, the study aims to determine effectiveness of video educational media increasing family support and adherence of hypertensive patients to undergo treatment process. Research is quasi-experimental and non-randomized pre-post for control group. The participants were determined by non-probability with 40 people for intervention group and 40 people as controls. The independent sample difference test used Mann-Whitney test and paired sample difference test used Wilcoxon Signed Ranks test. Determine effectiveness of intervention using N-Gain Score test. Results before intervention there was no significant difference between intervention and control groups regarding family support (Asymp. Sig. = 0.853), as well as regard level of adherence (Asymp. Sig. = 0.785). After intervention, there were significant differences regarding family support (Asymp. Sig. = 0.000) and level of adherence (Asymp. Sig. = 0.000). There were significant differences regarding family support and adherence, before and after the intervention, both in intervention and control groups (Asymp. Sig. = 0.000). Video is effective increasing family support (average 47.23%) and compliance (average 53.07%), with moderate effectiveness. The Randomized controlled trials (RCTs), the larger sample sizes, longer follow-up periods, and objectives and outcomes measurements face limitations in the study. Additional future needs to explore complementary intervention or multi-component approaches to optimize hypertension management and patient outcomes